Molecular‐based assessments of tribal and generic limits and relationships in Rubiaceae (Gentianales): Polyphyly of Pomazoteae and paraphyly of Ophiorrhizeae and Ophiorrhiza. Issue 1 (13th April 2019) - Razafimandimbison, Sylvain G.; Rydin, Catarina
Abstract: Circumscriptions of the Australasian tribes Ophiorrhizeae and Pomazoteae (Rubiaceae) as well as their generic relationships and limits have long remained unsettled. These tribes were originally delimited by Bremekamp based on the lack of raphides and testa cell patterns (thick‐ versus thin‐walled testa cells, respectively). Some authors have synonymized the two or treated Pomazoteae as a synonym of other tribes despite the fact that the matter has never been sufficiently addressed. We performed molecular phylogenetic analyses of Ophiorrhizeae sensu Bremer & Manen (i.e., comprising Coptophyllum, Lerchea, Neurocalyx, Ophiorrhiza, Spiradiclis and Xanthophytum ) based on sequence data from four plastid and two nuclear markers. Coptophyllum (= Pomazota, type of Pomazoteae), Lerchea and Xanthophytum together with seven other genera, were traditionally classified in Pomazoteae. We also investigated for the first time the two Pomazoteae genera Keenania and Leptomischus . Our analyses resolved Leptomischus as sister to the Rubioideae tribe Argostemmateae and we here formally classify this genus in that tribe. Ophiorrhizeae sensu Bremer and Manen is paraphyletic with respect to Keenania . Pomazoteae is polyphyletic, with most of its genera (including Coptophyllum ) belonging in Ophiorrhizeae. Its tribal status cannot be held. Testa cell patterns are evolutionarily labile, and seem to have no phylogenetic value at tribal level. Our study strongly supports a broadly delimited Ophiorrhizeae that contains mostly suffrutescent herbs. Within Ophiorrhizeae as here defined, Neurocalyx is sister to the rest of the tribe, followed by Xanthophytum . The Coptophyllum‐Lerchea clade is sister to a large clade formed by Keenania, Ophiorrhiza and Spiradiclis . Ophiorrhiza is paraphyletic with respect to Keenania and Spiradiclis, and was resolved in two well‐supported lineages, the Ophiorrhiza‐Keenania and Ophiorrhiza‐Spiradiclis lineages. Accordingly, we formally transferred all validly published names from Keenania and Spiradiclis to Ophiorrhiza, resulting in 40 new combinations and 15 new names.